Dietary nitrate increases arginine availability and protects mitochondrial complex I and energetics in the hypoxic rat heart. (7th October 2014) - Ashmore, Tom; Fernandez, Bernadette O.; Branco‐Price, Cristina; West, James A.; Cowburn, Andrew S.; Heather, Lisa C.; Griffin, Julian L.; Johnson, Randall S.; Feelisch, Martin; Murray, Andrew J.
<x xml:space="preserve">Abstract</x> Key points Exposure to environmental hypoxia, at high altitude or in a chamber, impairs cardiac energetics and alters mitochondrial function. Inorganic nitrate, a ubiquitous dietary constituent, improves mitochondrial efficiency, lowering the oxygen cost of exercise, whilst elevated circulating nitrogen oxide levels in high‐altitude natives enhances blood flow. Here we report that dietary nitrate supplementation prevents hypoxia‐induced changes in cardiac mitochondrial function and energetics, whilst ameliorating oxidative stress, suggesting improved tissue oxygenation. Furthermore, nitrate supplementation suppresses cardiac arginase expression and increases tissue l‐arginine levels under both hypoxic and normoxic conditions, underpinning a novel mechanism to enhance the availability of nitric oxide. Nitrate supplementation may thus be of benefit to individuals exposed to hypobaric hypoxia at altitude or in patients with diseases characterised by tissue hypoxia and energetic impairment, such as heart failure and chronic obstructive pulmonary disease, or in the critically ill. Abstract Hypoxic exposure is associated with impaired cardiac energetics in humans and altered mitochondrial function, with suppressed complex I‐supported respiration, in rat heart. This response might limit reactive oxygen species generation, but at the cost of impaired electron transport chain (ETC) activity. Dietary nitrate supplementation improves mitochondrial efficiency and can promote tissue oxygenation by enhancing blood flow. We therefore hypothesised that ETC dysfunction, impaired energetics and oxidative damage in the hearts of rats exposed to chronic hypoxia could be alleviated by sustained administration of a moderate dose of dietary nitrate. Male Wistar rats (n = 40) were given water supplemented with 0.7 mmol l−1 NaCl (as control) or 0.7 mmol l−1 NaNO3, elevating plasma nitrate levels by 80%, and were exposed to 13% O2 (hypoxia) or normoxia (n = 10 per group) for 14 days. Respiration rates, ETC protein levels, mitochondrial density, ATP content and protein carbonylation were measured in cardiac muscle. Complex I respiration rates and protein levels were 33% lower in hypoxic/NaCl rats compared with normoxic/NaCl controls. Protein carbonylation was 65% higher in hearts of hypoxic rats compared with controls, indicating increased oxidative stress, whilst ATP levels were 62% lower. Respiration rates, complex I protein and activity, protein carbonylation and ATP levels were all fully protected in the hearts of nitrate‐supplemented hypoxic rats. Both in normoxia and hypoxia, dietary nitrate suppressed cardiac arginase expression and activity and markedly elevated cardiac l‐arginine concentrations, unmasking a novel mechanism of action by which nitrate enhances tissue NO bioavailability. Dietary nitrate therefore alleviates metabolic abnormalities in the hypoxic heart, improving myocardial energetics.